Epoksidasi Karet Alam Dengan Menggunakan Surfaktan Amonium Lauril Sulfat Sebagai Wetting Agent - Donny Kurniawan; Nirwana Nirwana; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Epoxidation of natural rubber were tried to be produced under various conditions within in-situ epoxidation reaction. The use of ammonium lauryl sulphate (ALS) as wetting agent also the effect of hydrogen peroxide (H2O2) amount and the reaction temperature were discussed. The molar ratio values of the isoprene units of natural rubber to formic acid and H2O2 was set at 1:1:1, 1:1:2, and 1:1:3 while the temperature was varied by 40, 50 and 60o C. ALS that been used were 1 phr within 100 ml Latex NR that contained 20,52% DRC. The process reaction were using a reactor with stirrer and water bath for five hours. The results were shown in spectroscopy FT-IR instrument. From the preparation, we know that the natural rubber that been used had the same rubber content compare to the previous researcher. The molar ratio and temperature variation that have been used were not succed to made epoxidation group in natural rubber. The function of ALS as wetting agent at the preparation were not worked enough, so the epoxidized were not produced.Keywords: ALS, formic acid, H2O2, in-situ epoxidation